2015
DOI: 10.1128/aem.02089-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Cross-Feeding Interactions between Bifidobacterium longum subsp. longum NCC2705 and Eubacterium rectale ATCC 33656 Explain the Bifidogenic and Butyrogenic Effects of Arabinoxylan Oligosaccharides

Abstract: Arabinoxylan oligosaccharides (AXOS) are a promising class of prebiotics that have the potential to stimulate the growth of bifidobacteria and the production of butyrate in the human colon, known as the bifidogenic and butyrogenic effects, respectively. Although these dual effects of AXOS are considered beneficial for human health, their underlying mechanisms are still far from being understood. Therefore, this study investigated the metabolic interactions between Bifidobacterium longum subsp. longum NCC2705 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 62 publications
7
148
0
Order By: Relevance
“…Intriguingly, complex inter-species cross-feeding mechanisms have been described that link the metabolic activity of lactic acid bacteria (e.g., lactobacilli and bifidobacteria, key species generally considered to be probiotic, i.e. to promote host health) with butyrate-producing pathways (Belenguer et al, 2006;De Vuyst and Leroy, 2011;Flint et al, 2007;Rios-Covian et al, 2015;Rivière et al, 2015). In this context it is interesting to note that in extreme cases such as the short-bowel syndrome in humans, fermentation-derived overdoses of lactate (2-3mM in serum) can induce severe neurological symptoms (Ewaschuk et al, 2005), which might be treated by enhancing conversion of lactate to butyrate in the colonic lumen.…”
Section: The Microbiotamentioning
confidence: 98%
“…Intriguingly, complex inter-species cross-feeding mechanisms have been described that link the metabolic activity of lactic acid bacteria (e.g., lactobacilli and bifidobacteria, key species generally considered to be probiotic, i.e. to promote host health) with butyrate-producing pathways (Belenguer et al, 2006;De Vuyst and Leroy, 2011;Flint et al, 2007;Rios-Covian et al, 2015;Rivière et al, 2015). In this context it is interesting to note that in extreme cases such as the short-bowel syndrome in humans, fermentation-derived overdoses of lactate (2-3mM in serum) can induce severe neurological symptoms (Ewaschuk et al, 2005), which might be treated by enhancing conversion of lactate to butyrate in the colonic lumen.…”
Section: The Microbiotamentioning
confidence: 98%
“…Recently, several studies have revealed that bifidobacteria play an ecological role in shaping the gut murine microbiome toward a saccharolytic microbiota by means of crossfeeding activities (43,(74)(75)(76)(77)(78)(79). Cross-feeding activities target polysaccharides that reach the gut intact, where they may undergo extracellular hydrolysis by enteric bacteria like bifidobacteria, thus generating simple glycans (i.e., monosaccharides and oligosaccharides) that may become available to other microbial gut inhabitants (80).…”
Section: Figmentioning
confidence: 99%
“…In this context, various studies involving simple bifidobacterial communities have shown how saccharolytic bacteria may cooperate in order to obtain access to complex diet carbohydrates (e.g., starch, xylan, or arabinoxylan) (26,43,79) or hostderived carbohydrate (e.g., mucin and HMOs) (75,76,79). In such scenario, the cross-feeding activities exerted by bifidobacteria ultimately influence the gut microbiota composition as well as its functionality by enhancing the production of (certain) shortchain fatty acids (SCFA) directly or indirectly though the production of acetate, which is then converted to butyrate by a species of eubacteria (77)(78)(79).…”
Section: Figmentioning
confidence: 99%
“…Coculture experiments between Faecalibacterium prausnitzii and four different Bifidobacterium species showed that cross‐feeding interactions could be competitive or mutually beneficial, depending on the species involved (Moens et al ). Coculture experiments of Bifidobacterium longum and Eubacterium rectale on arabinoxylan oligosaccharides illustrated that butyrate production relied on the conversion of B. longum acetate by E. rectale (Rivière et al ). Studies in which labelled isotope was added to faecal batch cultures demonstrated that 80% of butyrate production relied on interconversion of acetate and lactate to butyrate (Morrison et al ).…”
Section: Impacts On the Microbiome—in Vitro And In Vivomentioning
confidence: 99%